2009
DOI: 10.1111/j.1574-6968.2008.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid-regulated genes inRhizobium etliCNPAF512

Abstract: In the rhizosphere and their interaction with plants rhizobia encounter many different plant compounds, including phytohormones like auxins. Moreover, some rhizobial strains are capable of producing the auxin, indole-3-acetic acid (IAA). However, the role of IAA for the bacterial partner in the legume-Rhizobium symbiosis is not known. To identify the effect of IAA on rhizobial gene expression, a transposon (mTn5gusA-oriV) mutant library of Rhizobium etli, enriched for mutants that show differential gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Moreover, IAA triggers an increased tolerance to stress conditions (heat and cold shock, UV-irradiation, osmotic and acid shock and oxidative stress) and toxic compounds (antibiotics, detergents and dyes) [61]. A recent research on Rhizobium etli showed that IAA addition regulates genes involved in plant signal processing, motility and attachment to plant roots, which clearly demonstrating a distinct role for IAA in legume-Rhizobium interactions [62].…”
Section: Indole Derivants Also Involve In Biofilm Formationmentioning
confidence: 98%
“…Moreover, IAA triggers an increased tolerance to stress conditions (heat and cold shock, UV-irradiation, osmotic and acid shock and oxidative stress) and toxic compounds (antibiotics, detergents and dyes) [61]. A recent research on Rhizobium etli showed that IAA addition regulates genes involved in plant signal processing, motility and attachment to plant roots, which clearly demonstrating a distinct role for IAA in legume-Rhizobium interactions [62].…”
Section: Indole Derivants Also Involve In Biofilm Formationmentioning
confidence: 98%
“…Rhizobia in addition to their intrinsic N 2 -fixing ability also facilitate plant growth by solubilizing soil phosphate (Alikhani et al 2006), producing phytohormones (Spaepen et al 2009), siderophores (Wani et al 2007), exo-polysaccharides ) and ACC-deaminase (Duan et al 2009). A great deal of information concerning the effects of herbicides on rhizobia and legumes is available.…”
Section: Introductionmentioning
confidence: 99%
“…Auxin regulates the expression of different genes in Rhizobium-legume interaction that involved in plant signal processing and attachment to plant roots. Moreover, changes in auxin balance in host plant are prerequisite for nodule organogenesis (Mathesius et al 1998;Spaepen et al 2009). In the present study, we demonstrated the effect of free living (nonsymbiotic) PGPR on the growth of a leguminous plant, i.e., Vigna radiata (mungbean).…”
Section: Introductionmentioning
confidence: 99%